Podcasts as emerging tool for medical education: a critical perspective - Vijay, Radhika; Gupta, Namita (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Podcasts have started knocking the educational doors after setting their feet strong in entertainment grounds. There has always been a trend to welcome and introduce new ideas and innovative ways in medical education for the benefit of students. No doubts, they are an emerging tool for education. The study aims to know and evaluate critically the students’ perspective about the novel aural technology and its relevance to be included in the curriculum. Methods: A sample size of 110 undergraduate medical students enrolled in two private post graduate coaching centres in metropolitan regions of Delhi was taken to conduct the study. A semi structured pen and paper questionnaire was created and made to be filled by the participants. Results: Aware students actively participated in the survey and shared their preferences and opinions, but many lacked knowledge and interest in the newly introduced and conveyed audio technology. This was a direct result of their surroundings, friends and family circle. Generally, there was a welcome response towards podcasts being in trend and to be included as a supplementary teaching tool along with present ongoing modes of education. Conclusions: Students’ opinion taken over from time to time is of great value to introduce modern educational reforms. Podcasts are a very effective add-on tool if introduced in medical education. There still exists a wide room for research and evidence-based use of this technology and much work needs to be done to actually add a new brick in the current structure of medical education.